PELATIHAN DASAR-DASAR PEMETAAN BAGI STAF DESA SE-KECAMATAN BOTUMOITO KAB. BOALEMO - Arthur Gani Koto (Universitas Muhammadiyah Semarang, 2017)
Effective and robust natural resource management requires accurate, integrated, and reliable geospatial information. Each village has the potential of both natural resources (SDA) such as land, water, climate, geographical environment, livestock, agriculture, mining, fisheries, and human resource potentials in the form of diverse cultures and interactions. The lack of reliable human resources, can lead to unstructured village databases, which may hamper development. In parallel, it is necessary to improve the skills and knowledge of human resources of the village apparatus in the introduction and training of mapping basics.The purpose of this devotion is twofold, namely to increase knowledge and skills in terms of mapping basics, and to create quality village apparatuses as geospatial information compilers. The method of execution is done two stages namely lecture and practice. At the end of the training, each participant gets the practice of basic mapping that has been taught from the beginning to digital map making. Evaluation results show that each participant has understood most of the material presented.Keywords: mapping, dulangeya, botumoito, gorontalo